Customer Experience, Emotional Marketing, and Customer Engagement in Customer Loyalty: Through Customer Satisfaction - Dony Wira Sanjaya; , Agus Fredy Maradona (Amkop Management Accounting Review (AMAR), 2025)
This study aims to investigate the influence of customer experience, emotional marketing, and customer engagement on customer satisfaction and customer loyalty, as well as the role of customer satisfaction as a mediator in the relationship between these variables and customer loyalty. Specifically, this study focuses on analyzing the direct and indirect influences between these variables to provide a more comprehensive understanding of the dynamics of customer satisfaction and loyalty. This study uses Structural Equation Modeling (SEM) based on Analysis of Moment Structures (AMOS) to test the hypotheses. The analysis stages include data normality testing, outlier identification, measurement model evaluation, and structural model evaluation. This study found that customer experience and customer engagement have a positive and significant effect on customer loyalty through customer satisfaction. Meanwhile, emotional marketing directly influences customer loyalty, but customer satisfaction does not act as a mediator in this relationship. The results of this study provide valuable insights for companies in developing effective marketing strategies to increase customer loyalty. By understanding the important role of customer experience, strong interactions, and deep emotional connections, companies can create a more holistic and integrated approach to satisfying customers and building long-term loyalty. This study contributes to the development of marketing theory and provides practical implications for companies in increasing customer loyalty.